Characteristics of α-amylase in bulb scales of tulip (tulipa gesneriana L.) - S. Komiyama (2018)
We conducted biochemical and molecular analysis of tulip amylase. Enzyme extract was obtained from the scales of tulip bulbs after cold treatment for forcing cultivation, and some characteristics of the amylase were investigated. The amylase activity was measured by iodine-starch method. The degradation of soluble starch produced a series of maltooligosaccharides with different sizes. This indicates that the amylase in tulip bulb scale is endotype α-amylase. The optimum pH for amylase activity was about 5.6. The enzyme activity was stable at neutral and alkaline pH (pH 5-10) at 4° for 24h, but the activity remarkably decreased in acidic pH (pH<4.5). The α-amylase requires Ca2+ for its activity and stability. The optimum temperature for 5 min incubation was about 75° in the presence of Ca2+. The addition of 2 mM or 20 mM of Cu2+, Hg2+ and Zn2 + inhibited the amylase activity, but Ca2+, Mg2 +, Fe2+, CO2+ and Ni2+ did not affect. A cDNA of α-amylase was obtained by RT-PCR method using the primer designed from the database of the amino acid and DNA sequences of amylases in higher plants. The deduced amino acid sequence of the α-amylase from tulip bulb scales has high similarity (identity 60%) to those of the rice and maize.